Environmental Inequality and Pollution Advantage among Immigrants in the United States - Bakhtsiyarava, Maryia (Appl Geogr, 2017)
Environmental inequality scholarship has paid little attention to the disproportional exposure of immigrants in the United States (U.S.) to unfavorable environmental conditions. This study investigates whether new international migrants in the U.S. are exposed to environmental hazards and how this pattern varies among immigrant subpopulations (e.g., Hispanics, Asian, European). We combine sociodemographic information from the American Community Survey with toxicity-weighted chemical concentrations (Toxics Release Inventory) to model the relationship between toxin exposure and the relative population of recent immigrants across Public Use Microdata Areas (PUMAs, n=2,054) during 2005–2011. Results from spatial panel models show that immigrants tend to be less exposed to toxins, suggesting resilience instead of vulnerability. This pattern was pronounced among immigrants from Europe and Latin America (excluding Mexico). However, our results revealed that Mexican immigrants are disproportionately exposed to environmental hazards in wealthy regions.